Polish young consumers' attitudes towards mobile phone brands - Dawid Gajda (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2020)
Consumers' attitudes are determined by many factors, one of which is a product brand. The objective of the paper is to present young consumers' attitudes towards mobile phone brands. The ABC model of attitudes is the theoretical framework for the study. The research method was a paper-and-pencil survey (PAPI) on the sample of 250 respondents aged 18-25. The research showed that it is just the name of the brand that can affect consumers' attitudes. It is a derivative of associations with the brands. The value of the attitude components is differentiated by brands. The affective component appeared to be the most important and the cognitive component - the least important. The findings show that gender and brand of respondents' mobile phones also differentiate the importance of components of young consumers' attitudes on the mobile phone market. Limitations and recommendations for further research are presented as well.
Keywords: M31; M37; 650; brand; brand image; consumer attitude; mobile phone market